The impact of resources management on the achievement of the national policy on the environment and environmental sustainability in Nigeria (2017)
The paper examines the negative impact of unchecked natural resource management on the achievement of the Nigerian National Policy on the Environment and environmental resources sustainability. The paper takes the view that lack of effective resource management and developmental activities by Nigerians are responsible for various environmental challenges confronting Nigeria with concomitant health problems and uncoordinated spatial development. The paper submits that various environmental challenges in Nigeria are anthropogenic in nature. It highlights in passing the provisions of the Federal Republic of Nigeria Constitution 1999 (as amended) and the Environmental Impact Assessment Act on natural resources exploitation and developmental activities. The paper concludes among others that the Nigerian Constitution provisions on the preservation of environmental natural resource is a mere directive and advocates for the amendment of relevant provisions in the Constitution as panacea to effective resource management in Nigeria.